(untitled) (Research, Society and Development, 2021)
Objective: to analyze the spatial relation through georeferencing and temporal trend of confirmed cases of PLHIV and/or diagnosed with AIDS in a municipality in southern Brazil. Methodology: Ecological study, with a population composed of HIV/AIDS cases notified between 2007 and 2018. In spatial analysis, global Moran spatial autocorrection was used, followed by local spatial autocorrelation indicators, bivariate Moran analyzes and Kernel density. The association between distribution of cases in the census sectors was assessed by the technique of analyzing spatial variations in temporal trends, in order to detect and infer differences in their temporal tendency. The data were processed and demonstrated using maps. Results: There was a progressive increase in infection during the period. In the map of clusters of cases, it was found that the referral clinic is located close to the location of the concentration of diagnoses. As for the distribution of mortality, a homogeneous panorama was evidenced. Through the technique of analysis of spatial variations in temporal trends, it was possible to interpret, from its internal temporal tendency, the degree of growth or reduction of HIV/AIDS cases over the years within the cluster, in this case referring to the central region, which is compared with the external trend, that is, the trend in the entire municipality that does not belong to this same cluster. Conclusion: The geographic information system proved to be a relevant technology to understand the social dynamics of HIV infection and contributed to the identification of priority areas for planning health actions.